MANAJEMEN BANDWIDTH UNTUK OPTIMALISASI JARINGAN DI SMK TELKOM SANDHY PUTRA MALANG - Prasetyo, Yaniko Dimas Yogo; Affandi, Luqman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Vocational High School Telkom Sandhy Putra Malang is the first Vocational Hight School that learn about IT in Indonesia. In every learning activities, this schools has used a computer in it. So, it need a high speed and stable internet connection to support itâs learning activities.And it has been 2 years, all of learning activities use computer. So, high speed and stable internet connection is needed to do some material download from student and teacher.So, for handling that needed, a bandwidth managemendt in Vocational High School Telkom Sandhy Putra Malang is very needed. That is how to build a load balancing and queue bandwidth.With that things, so the final pupose from developing bandwidth management is make any proses inside Vocational High School Telkom Sandhy Putra Malang run smoothly.Â Keywords:mikrotik,network optimization